Maine Conservation in an Age of Global Climate Change - Judd, Richard (Maine Policy Review, 2020)
Maine has been a key player in one of the most dramatic changes in conservation strategy since Gifford Pinchot coined the term in the 1890s as private nonprofit land trusts have become essential to the conservation movement in the state. Land trusts spearheaded the new approach to conservation by drawing together landowners, philanthropic organizations, state and federal agencies, older conservation organizations, and most importantly, ordinary citizens. Given its prominence in the land-trust movement, Maine has provided leadership in a second revolutionary trend as trust managers embraced the emerging science of ecosystem management.
Keywords: land trusts; ecosystem management